Design and Implementation Guidelines for a Modular Spectral-Domain Optical Coherence Tomography Scanner - Farid Atry; Israel Jacob De La Rosa; Kevin R. Rarick; Ramin Pashaie (International Journal of Optics)
In the past decades, spectral-domain optical coherence tomography (SD-OCT) has transformed into a widely popular imaging technology which is used in many research and clinical applications. Despite such fast growth in the field, the technology has not been readily accessible to many research laboratories either due to the cost or inflexibility of the commercially available systems or due to the lack of essential knowledge in the field of optics to develop custom-made scanners that suit specific applications. This paper aims to provide a detailed discussion on the design and development process of a typical SD-OCT scanner. The effects of multiple design parameters, for the main optical and optomechanical components, on the overall performance of the imaging system are analyzed and discussions are provided to serve as a guideline for the development of a custom SD-OCT system. While this article can be generalized for different applications, we will demonstrate the design of a SD-OCT system and representative results for in vivo brain imaging. We explain procedures to measure the axial and transversal resolutions and field of view of the system and to understand the discrepancies between the experimental and theoretical values. The specific aim of this piece is to facilitate the process of constructing custom-made SD-OCT scanners for research groups with minimum understanding of concepts in optical design and medical imaging.